"Cancer is in style": lifestyle change and the perceived impact of globalization on Andean indigenous communities in Ecuador. Issue 2 (17th February 2021) - Martinez Tyson, Dinorah; Teran, Enrique; Đào, Lillie Uyên-Loan; Chee, Vanessa; Hernández, Isabel; Flores, Mercedes; Reina Ortiz, Miguel; Izurieta, Ricardo; Baldwin, Julie A.
ABSTRACT: Introduction : There is a paucity of information on cancer among Indigenous populations in Latin America. Methods : Guided by tenets of community engaged research and syndemic theory, we conducted eight focus groups ( n = 59) with Kichwa men and women in the province of Imbabura, Ecuador. Data were analyzed using applied thematic analysis techniques. Results : Cancer emerged as an important health problem and was reported as a growing concern. Kichwa participants in this study attributed the rise in cancer to (1) exposure to chemicals and pesticides, (2) urbanization and development, and (3) the rise of innutritious, westernized diets. Conclusion : Our findings suggest that the Kichwa are attuned to the global phenomena in which traditional diet has been replaced by western, processed foods and fast food, which result in higher levels of chronic diseases such as cancer. More research is needed to understand the cancer burden among Indigenous peoples in Latin America.